Regulation of SUMOylation on RNA metabolism in cancers - Cao, Yingting; Huang, Caihu; Zhao, Xian; Yu, Jianxiu (Frontiers in Molecular Biosciences, 2023)
Post-translational modifications of proteins play very important roles in regulating RNA metabolism and affect many biological pathways. Here we mainly summarize the crucial functions of small ubiquitin-like modifier (SUMO) modification in RNA metabolism including transcription, splicing, tailing, stability and modification, as well as its impact on the biogenesis and function of microRNA (miRNA) in particular. This review also highlights the current knowledge about SUMOylation regulation in RNA metabolism involved in many cellular processes such as cell proliferation and apoptosis, which is closely related to tumorigenesis and cancer progression.